The Effect of Problem-Based Learning on Fourth-Grade Elementary School Students' Numeracy Skills - Saleha, Saleha; Elihami, Elihami (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Numeracy enables elementary school students to use mathematical knowledge to understand and solve contextual problems. This study aimed to analyze changes in the numeracy skills of fourth-grade students at UPT SDN 197 Pinrang before and after Problem-Based Learning and to test differences between pretest and posttest scores. A quantitative pre-experimental one-group pretest-posttest design was employed. Saturated sampling involved 27 fourth-grade students. Data were collected through observation, numeracy tests, and documentation and analyzed using descriptive statistics, the Shapiro-Wilk normality test, N-gain, and a paired-samples t-test. The findings showed a pretest mean of 63.93, with 12 students (44.44%) meeting the minimum mastery criterion of 70. The posttest mean increased to 87.83, and all students achieved mastery. Shapiro-Wilk significance values were .075 for the pretest and .063 for the posttest, indicating that the scores met the normality assumption. The mean N-gain was .5827, indicating improvement. The paired-samples t-test yielded t = 10.225, df = 26, and p < .001. The results demonstrate a statistically significant difference in numeracy performance after Problem-Based Learning. Because the study did not include a control group, causal interpretation should remain cautious.